2022
DOI: 10.1177/09697330221075779
|View full text |Cite
|
Sign up to set email alerts
|

Profiling nursing students’ dishonest behaviour: Classroom versus clinical settings

Abstract: Background While academic dishonesty among nursing students is becoming a global problem, the instruments used in studies on this topic are heterogeneous and, in many cases, not even validated. This makes it difficult or impossible to compare the findings on a global scale. Objectives To investigate the profile of Croatian nursing students’ dishonest behaviour in classroom and clinical settings and to examine the relationship between the incidence of dishonest behaviour in both settings. Research design A quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…[4,6,[8][9][10] In the classroom, nearly every Croatian nursing student (91.3%) engaged in dishonest behavior twice or more. [11] Another study found that up to 88% of South African nursing students admitted to engaging in dishonest behaviors at least once. [12] Further, the secondary account of observing other students cheating or indulging in academic dishonesty was high.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…[4,6,[8][9][10] In the classroom, nearly every Croatian nursing student (91.3%) engaged in dishonest behavior twice or more. [11] Another study found that up to 88% of South African nursing students admitted to engaging in dishonest behaviors at least once. [12] Further, the secondary account of observing other students cheating or indulging in academic dishonesty was high.…”
Section: Introductionmentioning
confidence: 99%
“…Unethical practices and cheating have been observed even in clinical settings, with about one-third of nursing students indulging in cheating during clinical duties. [ 11 ] There has been considerable research exploring unethical and dishonest practices and cheating in nursing students. Lovrić and Žvanut [ 11 ] reviewed original articles and summarized empirical evidence that the practice of cheating and dishonest methods is malignant among nursing students worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations